Performance of Chilli Varieties under Diverse Nutrient Management of Different Farming Systems - Jha, Anjali Kumari; Kumar, Prince; Jana, J. C.; Chatterjee, R.; Sarkar, R. K. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during November to April of 2024–25 at the Horticulture Instructional Farm of the Faculty of Horticulture, Uttar Banga Krishi Viswavidyalaya, Pundibari, Coochbehar, to evaluate the performance of chillies under diverse nutrient management of different farming systems. The main plot treatments consisted of four nutrient management practices, viz., farmer’s practice (FP), integrated nutrient management (INM), organic farming (OF) and natural farming (NF) and three varieties of chillies, viz., Kashi Abha (V1), Pusa Sadabahar (V2) and Kashi Anmol (V3), were described in subplots. Results of the experiment revealed that the integrated nutrient management (INM) recorded significantly higher plant height (67.21 cm), minimum days to 50% flowering (56.07 days), maximum days to last picking (172.94 days), maximum number of pickings (5.36), maximum number of green fruits per plant (99.83), fruit weight (4.25 g), green fruit yield plant-1 (431.21 g) and green fruit yield ha-1 (24.95 t) whereas NF took maximum days to 50% flowering as compared to other farming practices. Among the varieties, Pusa Sadabahar gave maximum plant height, days to 50% flowering, number of pickings, and number of green fruits per plant, and Kashi Anmol gave maximum days to last picking, average fruit weight, green fruit yield per plant, and green fruit yield per hectare. Despite a minimum number of green fruits per plant (81.65), fruit weight (3.75 g), green fruit yield plant-1 (291.03 g), and green fruit yield ha-1 (16.17 t), the highest benefit-cost ratio of 2.88 was obtained in the NF treatment.